Elevated Th1 and terminally differentiated cytotoxic T cells with suppressed Tc17 lymphocytes in lung tissue of advanced COPD and IPF patients undergoing lung transplantation - Šarc, Irena; Rijavec, Matija; Dejanović, Luka; Koren, Ana; Zimmermann, Matthias; Ankersmit, Hendrik J.; Korošec, Peter (Frontiers in Immunology, 2025)
IntroductionThe immunopathogenesis of end-stage chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF) remains poorly understood. Emerging evidence suggests that distinct T cell subpopulations may play critical roles in the progression of both diseases. A better understanding of these roles could provide important insights into underlying mechanisms and guide the development of targeted therapies.MethodsWe performed flow cytometric analysis of explanted lung tissue from patients with advanced COPD (n = 9), IPF (n = 9), and idiopathic pulmonary arterial hypertension (IPAH, n = 3) undergoing lung transplantation. Healthy donor lung tissue (n = 7) served as controls.ResultsBoth COPD and IPF lungs demonstrated an increased frequency of Th1 (CXCR3+CCR4-CCR6-) lymphocytes compared to controls. In contrast, Tc17 cells were significantly reduced. No notable differences were observed in Th2, Th17, or Tc1 cell populations. Activated CD4+ T cells (CD69+CD25+HLA-DR-/+) were significantly enriched in IPF compared to COPD and donor lungs. COPD lungs exhibited a marked expansion of terminally differentiated cytotoxic CD8+CD28-CD27- T cells. In double-negative (DN; CD3+CD4-CD8-) T cell compartment, CD25+ T cells were increased in COPD, whereas DN tissue-resident memory (TRM; CD69+CD25-HLA-DR-) cells were reduced in both COPD and IPF. Invariant natural killer T (iNKT; Vα24+Vβ11+) cell levels were uniformly low without intergroup differences.DiscussionOur findings identify disease-specific immune signatures in end-stage COPD and IPF. Th1 cell expansion together with a reduction in Tc17 and DN TRM subsets represented shared features of COPD and IPF, whereas accumulation of terminally differentiated cytotoxic CD8+ T cells and CD25+ DN T cells was specific to COPD. These findings enhance our understanding of adaptive immune dysregulation in COPD and IPF and may support the development of immunomodulatory strategies.